Enzyme‐Controlled Sensing–Actuating Nanomachine Based on Janus Au–Mesoporous Silica Nanoparticles. Issue 24 (6th May 2013) - Villalonga, Reynaldo; Díez, Paula; Sánchez, Alfredo; Aznar, Elena; Martínez‐Máñez, Ramón; Pingarrón, José M.
Abstract Novel Janus nanoparticles with Au and mesoporous silica faces on opposite sides were prepared using a Pickering emulsion template with paraffin wax as the oil phase. These anisotropic colloids were employed as integrated sensing–actuating nanomachines for enzyme‐controlled stimuli‐responsive cargo delivery. As a proof of concept, we demonstrated the successful use of the Janus colloids for controlled delivery of tris(2, 2'‐bipyridyl) ruthenium(II) chloride from the mesoporous silica face, which was grafted with pH‐sensitive gatelike scaffoldings. The release was mediated by the on‐demand catalytic decomposition of urea by urease, which was covalently immobilized on the Au face.